Faktor-Faktor yang Mempengaruhi Kepuasan dan Minat Beli Ulang serta Loyalitas Pengguna Tokopedia - Laura Kurniawan; Djajasukma Tjahjadi (Jurnal Sistem Informasi Bisnis, 2024)
Advances in technology have provided many conveniences in carrying out daily activities. One technology that is widely used today is online shopping as an application of the e-commerce system. One of the leaders of online shopping platform in Indonesia is Tokopedia. Tokopedia has received many awards, including Best Company in Consumer Industry in Indonesia Digital Economy Award in 2016 , and the Top 50 Most Valuable Indonesian Brands 2016 award. Along with the rapid development of the online shopping world, Tokopedia has to face its competitors. This paper is to study the factors influencing satisfaction which are trust, ease of use and service qualtity, and the factors influencing repurchase intention which are brand image, price perception, and promotion. The effect of satisfaction and repurchase intention on Tokopedia’s consumer loyalty was also studied. Using path-analysis method, 300 respondents were surveyed to test the research model. The result shows that trust, ease of use, service quality, were significantly has effect on customer satisfaction. Price has effect on repurchase intention, but brand image and promotion showed no effect. This study is also shows that customer satisfaction has no effect on customer loyalty, but repurchase intention has significant effect on customer loyalty.